Anemia among Pregnant Women at Nepalgunj Medical College - BC, Durga (Journal of Nepalgunj Medical College, 2022)
Introduction: Anemia in pregnancy is major health issue of developing countries responsible for adverse maternal and fetal outcome. According to World health organization pregnant women with hemoglobin level less than 11 gm/dl in first trimester and less than 10.5gm/dl in second and third trimester are considered to be anemic. Iron deficiency anemia is common during pregnancy followed by megaloblastic anemia. Aims: To find out the prevalence of anemia during pregnancy. To correlate the maternal and fetal complications associated with anemia during pregnancy. Methods: This is a prospective hospital based study done at department of obstetrics and gynecology Nepalgunj Medical College from July 2020 to January 2021. All pregnant women with hemoglobin level <11 gm/dl were enrolled in the study. Data were collected from antenatal clinic and biochemistry laboratory. Results: In this study maximum participants were of age group 20-25 consisting of 38.5%. Anemia was more common in multiparous i.e. 60% as compared to primipara i.e. 40%. In this study maximum participant had vaginal delivery (57%) followed by LSCS (29%) then instrumental delivery (14%). These ladies had complications like postpartum hemorrhage (27.7%), preterm labor (16.9%), pregnancy induced hypertension (9.2%). similarly 10.8% had sepsis and 20% had no complications. About 23.1% babies delivered by anemic ladies required neonatal intensive care. Intrauterine growth restriction was seen in 12.3%, preterm birth in 10.3% and 53.8% babies had no complications. Conclusion: The prevalence of anemia during pregnancy is high leading to adverse maternal and fetal outcome.